Analysis of methods for reactive power control - Ikromjon U. Rakhmonov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: Efficient management of reactive power is essential for ensuring voltage stability in power grids, reducing energy losses, and extending the lifespan of electrical equipment. Due to the dynamic nature of modern power system loads, traditional stationary compensation methods are no longer sufficient, leading to an increased need for automated and adaptive control systems. Objective: To analyze modern, economically and technically effective methods of reactive power compensation and automatic control, and to develop optimal real-time compensation solutions. Methods: Open-loop and closed-loop control schemes, Time-based control, Control based on voltage, current, and reactive power values, Phase-by-phase monitoring using phase regulators (e.g., B2201), Additional control systems based on non-electrical sensors (e.g., temperature, pressure) Results: Analysis shows that using automatic control systems can normalize grid voltage, significantly reduce energy losses, eliminate over- or under-compensation, and enhance system stability. Regulators like B2201 provide real-time reactive power compensation according to load characteristics